Early experience with the use of hepatitis C antibody‐positive, nucleic acid testing‐negative donors in lung transplantation. Issue 3 (8th February 2019) - Watson, Joshua; Mulvihill, Michael S.; Cox, Morgan L.; Rich, Lauren; Wolfe, Cameron R.; Gray, Alice; Hartwig, Matthew G.
Abstract: Historically, potential lung donors who have detectable antibodies to hepatitis C virus have been declined by most centers due to concern for possible disease transmission. We sought to evaluate hepatitis C viral transmission rates from donors who were known to be HCV Ab positive but HCV NAT negative. We performed a single‐center retrospective review of a prospectively collected database for lung transplant recipients at our center including HCV Ab+NAT‐ donors (approved January 2017). Donor and recipient demographic data were compiled, and records were queried to ascertain rate of seroconversion. During the study period (1/1/17 to 8/9/17), a total of 64 recipients underwent lung transplantation. Thirteen (20%) donors were HCV Ab+NAT‐. All recipients of HCV Ab+NAT‐ grafts were HCV Ab‐ at the time of transplant. Recipients of grafts from HCV Ab+NAT‐ donors underwent protocol NAT at 2 and 12 months and all are NAT‐ to date. One recipient developed reactive HCV Ab at 6 months post‐transplant. Follow‐up NAT showed HCV RNA to be undetectable. To date, use of HCV Ab+NAT‐ donors in lung transplantation has yielded favorable outcomes, with evidence of one transient seroconversion suggesting this practice may increase access to life‐saving transplantation to those in need.